Workforce agility and technological innovation enhancing sustainable lobster business in Indonesia - Utomo, Fajar Cahyo; Reztrianti, Diajeng; Rahmawantari, Dhistianti Mei; Uyun, Aep Saepul (Edelweiss Applied Science and Technology, 2025)
This research aims to explore the relationship between labor agility, technological innovation, and business sustainability in the lobster industry, specifically in Lobstamasta, Sawarna Village, Banten Province. With the significant contribution of the fishing industry to the national economy, this research emphasizes the importance of applying blue economy principles to increase productivity while preserving the environment. The research method used is a quantitative approach with a descriptive and analytical design, which relies on data collected from 60 respondents through a structured questionnaire. Data analysis was conducted using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) to test the relationship between variables. The results show that labor agility has a significant positive influence on technological innovation (coefficient 0.833) and business sustainability (coefficient 0.553). In addition, technological innovation contributes to business sustainability with a coefficient of 0.388 and acts as a significant mediator in the relationship between labor agility and business sustainability. These findings underscore the importance of improving labor agility and implementing technological innovation to achieve sustainability in the lobster farming sector.